Isokinetic quadriceps physiotherapy after knee surgery: a retrospective study - Nikolić, Siniša; Obradović, Borislav; Dimitrijević, Vanja; Rašković, Bojan; Dragičević-Cvjetković, Dragana (Frontiers in Rehabilitation Sciences, 2024)
Introduction Quadriceps weakness after knee surgery is the most common consequence that can have different consequences not only for the knee itself but also for the locomotor system in general. This study aimed to compare the results of isokinetic and isotonic exercise on torque restoration quadriceps on knee surgery. Methods A sample of 180 subjects was analyzed and divided into two subsamples according to the type of rehabilitation protocol that was implemented. The examined group A-isokinetic consisted of 90 male subjects aged 28.54 ± 4.44 years, with a rehabilitation protocol based on the isokinetic exercise of the quadriceps. The examined group B-isotonic also consisted of 90 male subjects aged 27.93 ± 4.27 years, with a rehabilitation protocol for strengthening the quadriceps that applied an exercise program with additional resistance, i.e., isotonic exercise in the gym. Before the start of the rehabilitation treatment, an initial isokinetic test was performed at an angular speed of 60 °/s in all subjects. After 3 and 6 weeks of rehabilitation treatment, the control tests were performed in the same way as in the initial test. Results Based on the values of MANOVA analysis and discriminative analysis, significantly better results of isokinetic tests were found in the examined group A-isokinetic compared with those in the examined group B-isotonic. At the final measurement of group A, 83 respondents (92.2%) were placed in the “biggest” class out of the 90 respondents. Conclusion Based on the obtained research results, we conclude that isokinetic exercise is more effective in terms of physiotherapy of quadriceps hypotrophy after knee surgery.